2022
DOI: 10.1183/23120541.00255-2022
|View full text |Cite
|
Sign up to set email alerts
|

Improving the wellbeing of caregivers of patients with COPD using a home-based pulmonary rehabilitation programme

Abstract: ObjectivesTo evaluate the effects of a home-based pulmonary rehabilitation (PR) programme on anxiety and depressive symptoms, general fatigue and burden in informal caregivers of patients with COPD. We also evaluated the baseline characteristics of both patients and caregivers that contributed to the change in caregiver's outcomes after PR.MethodsIn this retrospective study, patients with COPD were referred to an 8-week home-based PR programme consisting of a weekly supervised 90-minute session. Informal careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The intervention resulted in a significant improvement of all these descriptors. This study highlights the burden in caregivers and family members of patients with chronic respiratory diseases, and the importance of integrating caregivers into PR [23].…”
Section: Grosbois Et Al (Lille Francementioning
confidence: 90%
“…The intervention resulted in a significant improvement of all these descriptors. This study highlights the burden in caregivers and family members of patients with chronic respiratory diseases, and the importance of integrating caregivers into PR [23].…”
Section: Grosbois Et Al (Lille Francementioning
confidence: 90%
“…In daily clinical practice, this impact of the caring role is undervalued and not addressed by healthcare professionals. In fact, there is limited literature on interventions that include family and/or friend caregivers of people with COPD or ILD [ 9 , 13 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing family and/or friend caregivers as a cornerstone of the unit of care has been consistently advocated by palliative care in different chronic progressive diseases [ 7 , 21 ] and is clearly stated in the most recent recommendations for serious respiratory illness [ 18 , 22 ]. Less explored has been the role of PR to support family and/or friend caregivers [ 9 , 13 , 15 17 ]. To date, only one randomized controlled trial has been performed in this area [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…HBPR is an advanced strategy to reduce disease complications and improve independence and quality of life. It is particularly effective when patients have severe physical dysfunction, poor psychosocial status and limited access to healthcare services 16. A study showed that HBPR can reduce disease management costs, disease exacerbations, and need for hospital care, and improve quality of life 17.…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly effective when patients have severe physical dysfunction, poor psychosocial status and limited access to healthcare services. 16 A study showed that HBPR can reduce disease management costs, disease exacerbations, and need for hospital care, and improve quality of life. 17 Another study reported that HBPR reduced disease exacerbations and improved patient satisfaction, physical activity and quality of life.…”
Section: Introductionmentioning
confidence: 99%